Changing inequalities and societal impacts in rich countries: thirty countries' experiences (New York, 2014)
"There has been a remarkable upsurge of debate about increasing inequalities and their societal implications, reinforced by the economic crisis but bubbling to the surface before it. This has been seen in popular discourse, media coverage, political debate, and research in the social sciences. The central questions addressed by this book, and the major research project GINI on which it is based, are: - Have inequalities in income, wealth and education increased over the past 30 years or so across the rich countries, and if so why? - What are the social, cultural and political impacts of increasing inequalities in income, wealth and education? - What are the implications for policy and for the future development of welfare states? In seeking to answer these questions, this book adopts an interdisciplinary approach that draws on economics, sociology, and political science, and applies a common analytical framework to the experience of 30 advanced countries, namely all the EU member states except Cyprus and Malta, together with the USA, Japan, Canada, Australia and South Korea. It presents a description and analysis of the experience of each of these countries over the past three decades, together with an introduction, an overview of inequality trends, and a concluding chapter highlighting key findings and implications. These case-studies bring out the variety of country experiences and the importance of framing inequality trends in the institutional and policy context of each country if one is to adequately capture and understand the evolution of inequality and its impacts."